Life Modifications and PCOS: Old Story But New Tales - Gu, Yuanyuan; Zhou, Guannan; Zhou, Fangyue; Wu, Qiongwei; Ma, Chengbin; Zhang, Yi; Ding, Jingxin; Hua, Keqin (Frontiers in Endocrinology, 2022)
PCOS is defined as a kind of endocrine and metabolic disorder which affects females at reproductive ages. Lifestyle modifications, including diet modifications, exercise, and behavioral modification, appear to alleviate the metabolic dysfunction and improve the reproductive disorders of PCOS females (particular in obesity women). Therefore, lifestyle modifications have been gradually acknowledged as the first-line management for PCOS, especially in obese patients with PCOS. However, the mechanism of the lifestyle modifications in PCOS, the appropriate composition of diet modifications and the applicable type of exercise modifications for specific populations in females are rarely reported. We conducted a systematic review and enrolled ten randomized controlled trials for certain selection inclusion. In this review, we summarized the existing research on lifestyle modifications in PCOS. We aimed to illustrate the relationship between the lifestyle modifications and PCOS (referring to the hyperandrogenism, the insulin resistance as well as the obesity), and also considered the priorities for future research. These results might be an invaluable tool for guiding the lifestyle modifications as the intervention upon PCOS and other related endocrine disorders.